2002
DOI: 10.3184/030823402103171221
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 1,3,4-Oxadiazoles by Cyclisation of Acetoacetanilide Acylhydrazones under Mild Conditions

Abstract: Selective and efficient cyclisation of acetoacetanilide acylhydrazones into previously inaccessible 3-acetyl-2-anilinocarbonylmethyl-2,3-dihydro-2-methyl-1,3,4-oxadiazoles was achieved in acetic anhydride by use of acid catalysis at 40–50°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Dzvinchuk et al reported a synthesis of substituent 1,3,4‐oxadiazoles 180 by the acidic cyclization of acetoacetanilide acylhydrazones 178 . Heating 178 in Ac 2 O/TFA (v/v = 10/1) at 40–50 °C for 2–5 h, the enamine form 179 automatically cyclized to 180 in 55%–97% yields (Scheme 47) [91].…”
Section: Five‐membered Heterocycles Containing Multiple Heteroatomsmentioning
confidence: 99%
“…Dzvinchuk et al reported a synthesis of substituent 1,3,4‐oxadiazoles 180 by the acidic cyclization of acetoacetanilide acylhydrazones 178 . Heating 178 in Ac 2 O/TFA (v/v = 10/1) at 40–50 °C for 2–5 h, the enamine form 179 automatically cyclized to 180 in 55%–97% yields (Scheme 47) [91].…”
Section: Five‐membered Heterocycles Containing Multiple Heteroatomsmentioning
confidence: 99%